Low cycle fatigue behaviour of closed-cell aluminium foam - Ulbin, M. (2019)
The computational and experimental investigation of the fatigue behaviour of AlSi7 aluminium foam is presented in this study. The internal structure of a highly porous specimen was recorded using CT images to enable the subsequent detailed numerical modelling using the finite element method. A new approach for determination of the fatigue life of foam materials was developed, where the standardised approach is very difficult or even not possible to be used. In the proposed approach, several numerical models with different porosity were built and analysed instead of the numerical model, with real porosity of an actual porous structure. Stress-strain results obtained by the numerical analyses of these models were then used in the subsequent fatigue analysis to determine the fatigue lives of the treated porous specimens. Numerical results were compared with the experimental results, which were performed using low cycle fatigue testing under oscillating tensile loading with stress ratio R = 0.1. The developed approach enables the fatigue analyses and prediction of the fatigue lives of various porous structures where a real numerical model is very difficult to build because of its very complicated internal structure.